Grant-free random access for 6G mMTC in distributed-AP MIMO system - Chen, Shuqiao (Nanyang Technological University, 2024)
Massive Machine Type Communication (mMTC) is a major target use case for the sixth generation (6G) communications, which introduces challenges in multiple access schemes. In this dissertation, we introduce a grant-free random access (GFRA) system based on compressed sensing (CS), aiming to simultaneously satisfy massive connectivity in mMTC systems. It addresses the critical challenge of joint user activity detection (UAD) and channel estimation (CE) in GFRA systems with message-passing approach. Specifically, we first propose GFRA schemes in narrowband distributed access point (AP) multiple-input multiple-output (MIMO) systems with frequency flat fading channels, and develop a joint-UAD-CE receiver based on approximate message passing (AMP) and orthogonal approximate message passing (OAMP). Furthermore, we set the decision rule for UAD based on certain threshold. In addition, we extend the joint-UAD-CE study to wideband scenario with multipath frequency-selective fading channels, where a new system model utilizing orthogonal frequency division multiplexing (OFDM) scheme is introduced. We also adjust the AMP and OAMP algorithms in the corresponding wideband scenarios. Numerical results show that proposed methods attain high estimation and detection accuracy, which demonstrate that the proposed GFRA can accommodate the requirement of massive access.